Help‐seeking and Man Therapy: The impact of an online suicide intervention. Issue 1 (22nd November 2022) - Gilgoff, Jon N.; Wagner, Fernando; Frey, Jodi J.; Osteen, Philip J.
Abstract: Introduction: Suicide is a leading cause of death for men in the United States. Men traditionally have been hesitant to seek help, based on masculine norms of stoicism and self‐reliance, among other factors. Man Therapy (MT) is an online suicide prevention and mental health initiative that provides promise for facilitating male help‐seeking. Methods: This study draws on data from a randomized controlled trial which examined effects of MT on a sample of men residing in Michigan aged 25–64. The current study utilized logistic regression to test MT's effect on nonprofessional and professional help‐seeking, controlling for marital status, education, and sexual orientation. Results: A statistically significant positive association was found between MT and professional help‐seeking (OR = 1.55, p  = 0.049). A significant inverse association was also found with marital status, with partnered men less likely to seek professional help (OR = 0.53, p  = 0.007). There was no significant association between MT and nonprofessional help‐seeking. Conclusion: Man Therapy demonstrates the promise of web‐based suicide prevention efforts to reach men who typically do not engage in help‐seeking, providing a gateway to vital professional support. As technology continues to emerge, further suicide research is needed on use of this modality with working‐age men from diverse backgrounds.